2004
DOI: 10.1007/s10327-004-0134-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light conditions on prodigiosin stability in the biocontrol bacterium Serratia marcescens strain B2

Abstract: Serratia marcescens strain B2 is a potential biocontrol agent that produces the antibiotic pigment prodigiosin. When this strain was incubated under white or blue light conditions (Ͻ100 µmol m Ϫ2 s Ϫ1 ), prodigiosin concentration in bacterial cells decreased, but growth did not. However, red and far-red light had no effect on prodigiosin concentration in bacterial cells. Purified prodigiosin was degraded under white or blue light conditions but was not degraded under red and far-red light. Because white and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…However, very little is known about how different light regimes affect BCA when it comes to establishment in the plant canopy. One study demonstrated that, in Serratia marcescens, antibiotic pigment prodigiosin concentration in bacterial cells decreases under white and blue light (470 nm) conditions, but growth is not affected [168]. The same study showed that red and far-red light have no effect on the concentration of prodigiosin [168].…”
Section: Microbial Biocontrol Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, very little is known about how different light regimes affect BCA when it comes to establishment in the plant canopy. One study demonstrated that, in Serratia marcescens, antibiotic pigment prodigiosin concentration in bacterial cells decreases under white and blue light (470 nm) conditions, but growth is not affected [168]. The same study showed that red and far-red light have no effect on the concentration of prodigiosin [168].…”
Section: Microbial Biocontrol Agentsmentioning
confidence: 99%
“…One study demonstrated that, in Serratia marcescens, antibiotic pigment prodigiosin concentration in bacterial cells decreases under white and blue light (470 nm) conditions, but growth is not affected [168]. The same study showed that red and far-red light have no effect on the concentration of prodigiosin [168]. Another study [170] isolated the photolyase gene (phr1) from Trichoderma harzianum, a common soil fungus used as a BCA against phytopathogenic fungi [171] and investigated expression of phr1 when exposed to blue light.…”
Section: Microbial Biocontrol Agentsmentioning
confidence: 99%
“…To obtain the red pigments, strain 1020R was cultured in a medium containing 10 g/L of tryptone and 5 g/L of yeast extract in seawater (pH 7.8) at 28 C in the dark to avoid photodegradation of the pigments 15) on an orbital shaker for 2 d, and then without shaking for 6 d. The culture fluid was centrifuged, and the supernatant containing the red pigments was adjusted to pH 3.0 with HCl, and extracted with ethyl acetate. The red pigments in the pellet were extracted with ethanol.…”
mentioning
confidence: 99%
“…The production of prodigiosin by S. marcescens is influenced by numerous factors including inorganic phosphate availability, medium composition, temperature, pH, and natural components (Solé et al 1997;Hardjito et al 2002;Iranshahi et al 2004;Wei et al 2005). Specifically, light has an inhibiting and destructive effect on the production and stability of prodigiosin, and prodigiosin is considered to be capable of storing visible light energy (Ryazantseva et al 1995;Someya et al 2004). But S. marcescens TKU011 was reported to grow under illumination in shaking culture conditions, where it exhibited higher prodigiosin productivity than under dark conditions (Wang, 2012).…”
Section: Introductionmentioning
confidence: 99%